PENGARUH MASSAGE EFFLEURAGE TERHADAP KONTRAKSI UTERUS PADA PARTURIEN KALA I FASE AKTIF DI RSIA MELINDA KEDIRI - Astika Gita NIngrum (STRADA : Jurnal Ilmiah Kesehatan, 2012)
Massage on abdomen (effleurage) is a skin stimulation used during the birth process that can increases the production of oxytocin which is an important factor in the onset of inadequate uterine contractions and cause a relaxing effect. The purpose of this study is to determine the effleurage massage on uterine contractions in the active phase of first stage labour. Design used in this study was pre-experiment (one-group pretest-posttest designed). The population of this research is all parturient in the active phase of first stage labour in RSIA Melinda for a month. The number of samples used is 10 respondents taken by accidental sampling according to the inclusion criteria. Data collection techniques used observation sheet. The data obtained and analyzed using statistical tests (Mc Nemar Test) with α = 0.05. The results of this research showed that χ2 calculate = 2.25 <χ2 table = 3.84, that effleurage massage had not affected to uterine contraction of parturient in the active phase of first stage labour. By analytical, there were affected of massage effleurage to uterine contraction, but by This research, it is expected to be input in order to provide of research give effleurage massage when parturient enter the first stage inpartu active and for other researchers are expected to examine the massage effleurage or uterine contractions by considering research time and the factors that affect the contractions.